FUNGSI TALEMPONG PACIK DALAM UPACARA PERKAWINAN MASYARAKAT NAGARI KOTO ANAU - Suhanda Suhanda; Marzam Marzam; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2013)
Abstract There are types and variation of musical arts, one of them is traditional musical instrument Talempong Pacik which still exists in the pageant of wedding ceremony in Nagari Koto Anau. Talempong pacik is a type of percussion musical instrument which belongs to the traditional ensemble music of Minangkabau. This study is aimed at describing and finding the functions of Talempong pacik in the bridal pageant in the wedding ceremony. This is a qualitative research by using descriptive methods, describing the phenomena among the variables of data in form of words or images. The object of this research is Talempong Pacik musical instruments performed in the wedding ceremony. This research analyzes the functions of these instruments in the pageant procession of wedding ceremony in Nagari Koto Anau. Talempong Pacik in the pageant functions as (1) a means of entertainment for the community in terms of entertainment which gives specific meanings and messages in Minangkabau view. (2) a means of communication and information in the weeding procession in Nagari Koto Anau. This music is able to convey the message about the activity being performed and the message can be understood by the people who watched and listened to. Kata Kunci : Fungsi, Talempong pacik, Upacara, Perkawinan